The Absolute and Relative Pessimistic Inductions. - Seungbae Park (Problems / Problemos, 2019)
The absolute pessimistic induction states that earlier theories, although successful, were abandoned, so current theories, although successful, will also be abandoned. By contrast, the relative pessimistic induction states that earlier theories, although superior to their predecessors, were discarded, so current theories, although superior to earlier theories, will also be discarded. Some pessimists would have us believe that the relative pessimistic induction avoids empirical progressivism. I argue, however, that it has the same problem as the absolute pessimistic induction, viz., either its premise is implausible or its conclusion does not probably follow from its premise.